Conditioned medium from mesenchymal stem cells alleviates endothelial dysfunction of vascular grafts submitted to ischemia/reperfusion injury in 15-month-old rats - Korkmaz-İçöz, Sevil; Sun, Xiaoxin; Li, Shiliang; Brlecic, Paige; Loganathan, Sivakkanan; Ruppert, Mihály; Sayour, Alex Ali; Radovits, Tamás; Karck, Matthias; Szabó, Gábor (Cells, 2021)
In patients undergoing coronary artery bypass grafting (CABG), ischemia/reperfusion injury (IRI) is the main contributor to organ dysfunction. Aging-induced vascular damage may be further aggravated during CABG. Favorable effects of conditioned medium (CM) from mesenchymal stem cells (MSCs) have been suggested against IRI. We hypothesized that adding CM to saline protects vascular grafts from IRI in rats. We found that CM contains 28 factors involved in apoptosis, inflammation, and oxidative stress. Thoracic aortic rings from 15-month-old rats were explanted and immediately mounted in organ bath chambers (aged group) or underwent 24 h of cold ischemic preservation in saline-supplemented either with vehicle (aged-IR group) or CM (aged-IR+CM group), prior to mounting. Three-month-old rats were used as referent young animals. Aging was associated with an increase in intima-to-media thickness, an increase in collagen content, higher caspase-12 mRNA levels, and immunoreactivity compared to young rats. Impaired endothelium-dependent vasorelaxation to acetylcholine in the aged-IR group compared to the aged-aorta was improved by CM (aged 61 ± 2% vs. aged-IR 38 ± 2% vs. aged-IR+CM 50 ± 3%, p < 0.05). In the aged-IR group, the already high mRNA levels of caspase-12 were decreased by CM. CM alleviates endothelial dysfunction following IRI in 15-month-old rats. The protective effect may be related to the inhibition of caspase-12 expression.